Memory's Fatal Lure: The Left, the Congress and `Jeevan' in Kerala - J\Devika (Economic & Political Weekly EPW july 26, 2008, 2008)
The raging controversy in Kerala over the secularism content in one chapter of a school textbook brings back memories of similar controversies from the 1950s. Caste groups are protesting in defence of upper caste interests and religious organisations are angry at what they see as the state government crossing the limits in a discussion of secularism.On the other side, the spirit of rationalism which was earlier espoused by the radical anti-caste reformers is missing; now even the left has had to accommodate the demands of the powerful community organisations.